Case Report: Custom made 3D implants for glenoid tumor reconstruction should be designed as reverse total shoulder arthroplasty - Evrard, Robin; Ledoux, Antoine; Docquier, Pierre-Louis; Geenens, Florine; Schubert, Thomas (Frontiers in Surgery, 2024)
Background and objectivesIsolated bone tumors of the glenoid are exceedingly rare occurrence and pose a substantial surgical challenge. 3D printing technology has been proved to be a reliable tool to reconstruct complex anatomical part of the skeleton. We initially used this technology to reconstruct the glenoid component of the shoulder in a hemiarthroplasty configuration. We subsequently changed to a reverse shoulder arthroplasty.MethodsTwo patients were reconstructed with a hemiarthroplasty and 2 with a reverse configuration. Patients files were reviewed for radiographic analysis, pain and function scores.ResultsMean follow-up was 36.44 ± 16.27 months. All patients are alive and disease free. The two patients who benefitted from a hemiarthroplasty demonstrated a rapid deterioration of the proximal humeral articular surface. Given their pain and function scores, they subsequently required revision towards a total shoulder arthroplasty. Following this conversion, one patient presented a shoulder dislocation requiring surgical reintervention. We did not observe any loosening or infection in this short series.ConclusionsCustom made glenoid reconstruction should be designed as a reverse shoulder arthroplasty given the mechanical constrains on the proximal humerus and the extent of the surgery invariably damaging the suprascapular neurovascular bundle.